The Anti-virulence Efficacy of 4-(1,3-Dimethyl-2,3-Dihydro-1H-Benzimidazol-2-yl)Phenol Against Methicillin-Resistant Staphylococcus aureus - Tharmalingam, Nagendran; Khader, Rajamohammed; Fuchs, Beth Burgwyn; Mylonakis, Eleftherios (Frontiers in Microbiology, 2019)
Antimicrobial drug discovery against drug-resistant bacteria is an urgent need. Beyond agents with direct antibacterial activity, anti-virulent molecules may also be viable compounds to defend against bacterial pathogenesis. Using a high throughput screen (HTS) that utilized, Caenorhabditis elegans infected with methicillin-resistant Staphylococcus aureus (MRSA) strain of MW2, we identified 4-(1,3-dimethyl-2,3-dihydro-1H-benzimidazol-2-yl)phenol (BIP). Interestingly, BIP had no in vitro inhibition activity against MW2, at least up to 64 µg/mL. The lack of direct antimicrobial activity suggests that BIP could inhibit bacterial virulence factors. To explore the possible anti-virulence effect of the identified molecule, we first performed real-time PCR to examine changes in virulence expression. BIP was highly active against MRSA virulence factors at sub-lethal concentrations and down-regulated virulence regulator genes, such as agrA and codY. However, the benzimidazole derivatives omeprazole and pantoprazole, did not down-regulate virulence genes significantly, compared to BIP. Moreover, the BIP-pretreated MW2 cells were more vulnerable to macrophage-mediated killing, as confirmed by intracellular killing and live/dead staining assays, and less efficient in establishing a lethal infection in the invertebrate host Galleria mellonella (p=0.0131). We tested the cytotoxicity of BIP against human red blood cells (RBCs), and it did not cause hemolysis at the highest concentration tested (64 µg/mL). Taken together, our findings outline the potential anti-virulence activity of BIP that was identified through a whole animal based C. elegans-based screen.